A narrative review on perioperative systemic therapy in non-small cell lung cancer - Robert Hsu; Zhaohui Liao Arter; Darin Poei; David J. Benjamin (Open Exploration Publishing Inc., 2024)
Non-small cell lung cancer (NSCLC) that is operable still carries a high risk of recurrence, approaching 50% of all operable cases despite adding adjuvant chemotherapy. However, the utilization of immunotherapy and targeted therapy moving beyond the metastatic NSCLC setting and into early-stage perioperative management has generated tremendous enthusiasm and has been practice-changing. Adjuvant atezolizumab in NSCLC first demonstrated a clinical benefit with an immune checkpoint inhibitor. Then, with studies studying a significant benefit in major pathologic response in surgical patients treated preoperatively with immunotherapy compared to only chemotherapy, neoadjuvant nivolumab and chemotherapy were evaluated and showed significant event-free survival benefit leading to subsequent studies evaluating perioperative immunotherapy and chemotherapy. Meanwhile, with regards to targeted therapies, adjuvant osimertinib in EGFR-mutated NSCLC and adjuvant alectinib in ALK-rearranged NSCLC have both received regulatory approvals following demonstrated clinical benefit in clinical trials. With rapidly evolving changes in the field, new combinations such as multiple immunotherapy agents and antibody-drug conjugates in development, perioperative NSCLC management has quickly become complicated with different pathways to perioperative treatment. Furthermore, circulating tumor DNA and studies looking at better tools to prognosticate immunotherapy response will help with decision-making regarding which patients should receive immunotherapy and if so, either only pre-operatively or both pre- and post-operatively. In this review, we look at the evolution of systemic therapy in the perioperative setting from adjuvant chemotherapy to adjuvant immunotherapy to perioperative immunotherapy and look at perioperative targeted therapy while looking ahead to future considerations.